Genetic Encoding of Photocaged Cysteine Allows Photoactivation of TEV Protease in Live Mammalian Cells - Nguyen, Duy P. (J Am Chem Soc, 2014)
[Image: see text] We demonstrate the evolution of the PylRS/tRNA(CUA) pair for genetically encoding photocaged cysteine. By characterizing the incorporation in Escherichia coli and mammalian cells, and the photodeprotection process in vitro and in mammalian cells, we establish conditions for rapid efficient photodeprotection to reveal native proteins in live cells. We demonstrate the utility of this approach by rapidly activating TEV protease following illumination of single cells.